Programmable Spin–Orbit Torque Multistate Memory and Spin Logic Cell - Fan, Yibo; Han, Xiang; Zhao, Xiaonan; Dong, Yanan; Chen, Yanxue; Bai, Lihui; Yan, Shishen; Tian, Yufeng (ACS nano, 2022)
Controllable spin–orbit torque based nonvolatile memory is highly desired for constructing energy efficient reconfigurable logic-in-memory computing suitable for emerging data-intensive applications. Here, we report our exploration of the IrMn/Co/Ru/CoPt/CoO heterojunction as a potential candidate for applications in both multistate memory and programmable spin logic. The studied heterojunction can be programmed into four different magnetic configurations at will by tuning both the in-plane exchange bias at the interface of IrMn and Co layers and the out-of-plane exchange bias at the interface of CoPt and CoO layers. Moreover, on the basis of the controllable exchange bias effect, 10 states of nonvolatile memory and multiple logic-in-memory functions have been demonstrated. Our findings indicate that IrMn/Co/Ru/CoPt/CoO multilayered structures can be used as a building block for next-generation logic-in-memory and multifunctional multidimensional spintronic devices.